Os Sentidos do Trabalho para Trabalhadores Jovens: Uma análise com aprendizes na região metropolitana de Belo Horizonte (Management and Connections Journal, 2023)
Understanding the meanings of work is a challenge for managers given the increasingly transitory work relationships and individual-organization bonds. Thus, the objective of this article is to understand the meanings attributed to work by young people who work as apprentices in organizations in the metropolitan region of Belo Horizonte, Minas Gerais. Data were collected from interviews and submitted to content analysis. The results indicate that work occupies a central position in the lives of the young people interviewed, above all, for ensuring their livelihood and meeting some needs. The attribution of meanings to the work involved: representations about the work performed; social support/legitimacy; financial compensation; some degree of autonomy to carry out the activities; and professional expectations. It is concluded that the lack of professional experience in formal activities associated with the socioeconomic reality of individuals can affect the conception of the meanings of work.